2021
DOI: 10.3390/molecules27010089
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Biphenylcarbazole (CBP) with Siloxane-Hybrid Chains for Solvent-Free Liquid Materials

Abstract: We report herein the synthesis of siloxane-functionalized CBP molecules (4,4′-bis(carbazole)-1,1′-biphenyl) for liquid optoelectronic applications. The room-temperature liquid state is obtained through a convenient functionalization of the molecules with heptamethyltrisiloxane chains via hydrosilylation of alkenyl spacers. The synthesis comprises screening of metal-catalyzed methodologies to introduce alkenyl linkers into carbazoles (Stille and Suzuki Miyaura cross-couplings), incorporate the alkenylcarbazoles… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
(90 reference statements)
0
5
0
Order By: Relevance
“…The different siloxane-functionalized CBP derivatives investigated in this study were synthesized using optimized catalytic methodologies recently reported elsewhere (Scheme 1) [38]. Briefly, monobromocarbazole 1 was used to prepare the two CBP derivatives functionalized with two siloxane segments (short: CBP-2Si 3 and longer: CBP-2Si n ).…”
Section: Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…The different siloxane-functionalized CBP derivatives investigated in this study were synthesized using optimized catalytic methodologies recently reported elsewhere (Scheme 1) [38]. Briefly, monobromocarbazole 1 was used to prepare the two CBP derivatives functionalized with two siloxane segments (short: CBP-2Si 3 and longer: CBP-2Si n ).…”
Section: Synthesismentioning
confidence: 99%
“…The detailed synthetic protocols can be found in Ref. [38] or in the Supplementary Materials. stoichiometry of reagents in the first and third steps, leading to intermediates 4, 7, and the final CBP derivative (CBP-4Si3) functionalized with 4 short siloxane segments instead of 2.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several catalysts have been reported to be effective in the hydrogenation of SBR [11,12]. Barrios et al utilized a Ziegler-Natta-type catalyst made from a reaction between NiAcAc and n-BuLi to selectively hydrogenate 1,2-vinyl and 1,4-trans bonds in a styrene-butadiene copolymer [13].…”
Section: Introductionmentioning
confidence: 99%
“…CYPs are responsible for the metabolism of about 90% of administered drugs in men [ 4 ]. CYP enzymes were reported to catalyze a wide array of important chemical reactions such as arene oxidation, activation of inert C–H bonds, C–C coupling, epoxidation, hydroxylation, and N-dealkylation reactions [ 1 , 2 , 5 , 6 , 7 , 8 , 9 , 10 ]. In particular, hydroxylation reactions by CYP enzymes are among the most vital reactions in drug metabolism [ 3 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%